Rhizomatic Explorations in Curriculum - Smitka, Julie A. M. (Alberta Journal of Educational Research, 2012)
A visual and theatrical exercise anchored in the Grades 11 and 12 Ontario Curriculum for Media Arts and Interdisciplinary Studies was enacted and recorded as individual experiences of each participant. The event was re-mastered in a graphic representation that depicts the forces, pushes and pulls of curriculum and students’ needs which educators experience on a daily basis. Students participating in a co-educational public high school course were photographed alongside their yearbook advisor to examine the methodology of a/r/tography, embodiment and time/space/place during a staged photo shoot session. Participants, including the author, documented their experiences of this research creation event through written and photographic feedback. The basic findings resulted in the creation of the Dimension of the Mind Embodied (DOME), a new theory I coined that builds on Deleuze and Guattari’s (1987) concept of the rhizome. Chaque participant à un programme d'études en arts des médias et études interdisciplinaires de l'Ontario pour les 11e et 12e années a interprété un exercice visuel et théâtral. L'évènement a été remasterisé en une représentation graphique illustrant tant les forces et les mouvements en opposition du programme d'études que les besoins des élèves auxquels font face les enseignants à chaque jour. On a photographié des élèves qui suivaient un cours dans une école secondaire publique mixte à côté d'un conseiller de sorte à étudier l'a/r/tographie, la concrétisation et le temps/l'espace/le lieu pendant une session de photos publique. Les participants, y compris l'auteur, ont documenté leurs expériences relatives à cet évènement de création en produisant de la rétroaction écrite et photographique. De ces résultats a découlé la création de Dimension of the Mind Embodied (DOME), une nouvelle théorie que j'ai inventée à partir du concept de rhizome de Deleuze et Guattari (1987).